PENGARUH PENEMPATAN PEGAWAI, FASILITAS DAN KOMITMEN TERHADAP MOTIVASI KERJA PEGAWAI BADAN PENGELOLA KEUANGAN, PENDAPATAN DAN ASET DAERAH KOTA TANJUNGBALAI - Herianti Sirait; Dewi Sitio; Muhammad Ichsan Prawira (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study is whether the placement of employees, facilities, and commitment simultaneously has a positive and significant effect on the work motivation at Regional Financial Management, Income and Assets Agency, Kota Tanjungbalai. This study aims to determine the effect of employee placement, facilities and commitment to work motivation at Regional Financial Management, Income and Assets Agency, Kota Tanjungbalai. The sample in this study were all employees at Regional Financial Management, Income and Assets Agency, Kota Tanjungbalai, which numbered 46 people. The data analysis technique in this research is Multiple Linear Regression. The results of this study indicate; Employee placement partially has a positive and significant effect on employee motivation; Facilities partially have a positive and significant effect on employee motivation; Commitment partially has a positive and significant effect on employee motivation; Employee placement, facilities and commitment simultaneously have a positive and significant effect on employee motivation.